Clinical applicability of indirect resins: a literature review (Research, Society and Development, 2020)
Introduction: Indirect composites, or ceromers, have a better resistance, a greater increase in the conversion of monomers to polymers due to the possibility of complementary polymerization, better finishing and polishing, reduction of problems related to polymerization shrinkage when compared to direct composite resins. However, doubts still exist regarding the use, indication, and longevity of ceromers. Objective: The aim of this study was to conduct a literature review in order to analyze the existing scientific evidence on indirect composites. Method: Scientific articles in Portuguese and English published in the last 20 years were used, in addition to reference articles on the topic. The databases for consultation were Medical Publications (PUBMED), Scientific Electronic Library Online (SCIELO) and complementary books. Conclusion: According to the bibliographic survey, the indirect composite resins have characteristics that indicate to be a good restorative option, and are indicated for indirect restorations, such as total crowns, Class II or Class V cavities, aesthetic area and mainly in onlay/inlay restorations.